PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU YANG DIMEDIASI OLEH LOYALITAS GURU (Studi Pada Guru SDN Ploso V Kota Surabaya) - Shandy Kusuma Wardhana; Chamariyah Chamariyah; Subijanto Subijanto (Universitas 45 Surabaya, 2022)
The results showed that 1.) Leadership style had a significant positive effect on teacher performance with the original sample value of 0.490. 2.) Leadership style has a significant positive effect on loyalty with the original sample value of 0.501. 3.) Organizational culture has a significant positive effect on loyalty with the original sample value of 0.426. 4.) Organizational culture has a significant positive effect on teacher performance with the original sample value of 0.407. 5.) Loyalty has a significant positive effect on teacher performance with an original sample value of 0.664. 6.) Leadership style has a significant positive effect on teacher performance mediated by loyalty with an original sample value of 0.332. 7.) Organizational culture has a significant positive effect on teacher performance mediated by loyalty with an original sample value of 0.270.